TRUCK FOR HIGH-SPEED PASSENGER WAGONS OF UKRAINIAN RAILWAYS - Prykhodko, V. I.; Korobka, B. O.; Radzykhovskyi, O. O.; Shkabrov, O. O. (Science and Transport Progress, 2004)
The description of bogie for high-speed passenger cars of Ukrainian railways is adduced